Rozwijanie krytycznego myślenia w perspektywie glottodydaktycznej - Sujecka-Zając, Jolanta (Neofilolog, 2025)
Critical thinking is among the key 21st-century competencies, alongside creativity, collaboration, and effective communication. Its complex nature presents significant research and pedagogical challenges due to varying theoretical perspectives and inconsistent definitions of its components. For effective pedagogical intervention in language classes, we must first identify which elements of critical thinking can be developed and then determine appropriate teaching techniques and evaluation strategies. This paper examines selected conceptions of critical thinking that are particularly relevant to foreign language teaching and learning, with special attention to John Dewey’s foundational ideas. Two essential questions guide this exploration: “How should critical thinking be taught?” and “How should its development be assessed?” The “learning progressions” framework will be used to address these questions. The analysis incorporates examinations of existing language teaching materials and presents an original proposal for tasks specifically designed for French language instruction. By clarifying the relationship between critical thinking and language education, this work aims to provide practical guidance for language teachers seeking to foster this crucial competency in their classrooms.